2010
DOI: 10.1007/s11999-010-1383-8
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Articular Surface of One-piece Cups: A Cause of Runaway Wear and Early Failure

Abstract: Background Despite the clinical success of modern metal-on-metal articulations, concerns with wear-related release of metal ions persist. Evidence suggests metal ion release is related to the effective coverage of the head in the metal shell (the cup's functional articular arc). A recent study suggests a reduced functional articular arc is associated with increased ion release and the arc is a function of component design, size, and the abduction angle. Questions/purposes The purposes of this study were to (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 18 publications
(34 reference statements)
4
43
1
Order By: Relevance
“…Survival rates in our study also were worse than those reported by Langton et al [14]. We believe this is because our cohort included only patients with a small femoral head size, meaning that our patients were more prone to edgeloading as a result of a reduced functional arc [10]. Therefore, failure resulting from increased wear originating from the bearing surface instead of the taper is likely to be more prevalent in our cohort.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Survival rates in our study also were worse than those reported by Langton et al [14]. We believe this is because our cohort included only patients with a small femoral head size, meaning that our patients were more prone to edgeloading as a result of a reduced functional arc [10]. Therefore, failure resulting from increased wear originating from the bearing surface instead of the taper is likely to be more prevalent in our cohort.…”
Section: Discussioncontrasting
confidence: 51%
“…Functional arc of the cup increases with increasing head sizes [10] thus offering more cup coverage and decreasing the occurrence of edgeloading. Thus, especially in patients with large head implants in hip resurfacing, the prevalence of adverse reactions may be lower than in our current cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Micrometer measurements of internal liner geometry provided cup-face angles (CFA), cup-bearing angles (CBA), ROM, and polar-impingement angles (Fig. 1A) [9,23]. Liners were replicated in silicon (Aquasil-LV TM ; Densply, Milford, DE, USA) and the replicas sectioned for scanning electron microscopy (SEM) analysis (Fig.…”
Section: Standard Radiography and Eosmentioning
confidence: 99%
“…Many studies focused on cobalt-chromium (CoCr) alloys, cup designs ( Fig. 1), surgical positioning, and effects of ''edge loading'' [12,23,29,38,58,59,76]. Additionally, impingement, subluxation, and dislocation have always been unpredictable risk considerations [3,18,22,24,27,28,31,43,52,66,72,74,77,80].…”
Section: Introductionmentioning
confidence: 99%
“…This certainly applies to many women, but not all of them. Additionally, not all hip resurfacing devices have the same coverage of the head by the socket [2] and such differences in the small sizes can greatly affect the outcome of hip resurfacing arthroplasty. This is particularly important in our overly litigated society because every time a publication is made that suggests female gender is a risk factor, it reinforces the use of simplistic treatment algorithms and perfectly suitable female patients get denied the opportunity to be treated with hip resurfacing arthroplasty.…”
Section: W E Read the Study Bymentioning
confidence: 99%